Peptide/Antibody-Drug Conjugates for Therapeutic Applications in Inflammatory Disease - Jang, Yeongji; Choi, Jiwoong; Ryu, Youngri; Song, Hyun Kyu; Shim, Man Kyu; Yang, Yoosoo (Wiley-VCH, 2025)
Peptide/antibody–drug conjugates (PADCs) are an emerging class of targeted therapeutics that leverage the specificity of peptide or antibody ligands to deliver potent small-molecule payloads selectively to disease sites via cleavable linkers. This design combines high target affinity with controlled local activation and minimal systemic toxicity. To date, 15 antibody–drug conjugates and 3 peptide–drug conjugates have been approved by the FDA; however, all are indicated exclusively for oncology. Consequently, the development of PADCs has primarily focused on cancer, with relatively few comprehensive reviews addressing their potential in non-oncological applications. In this review, the therapeutic potential of PADCs as a targeted strategy for treating inflammatory diseases—such as inflammatory bowel disease, chronic kidney inflammation, and arthritis—is explored by detailing how engineered peptide or antibody ligands recognize upregulated pathological markers in inflamed microenvironments and enable site-specific drug release through stimuli-responsive linkers. By consolidating recent advances, this review broadens the therapeutic scope of PADCs and highlights their promise as next-generation immunomodulators for targeted treatment of inflammatory diseases.